Assessing the Longitudinal Change in Low Vision: A Test of Competing Hypotheses. (March 2021) - Liew, Hui-Peng
Introduction: Visual impairment among older adults has increasingly become one of the biggest challenges to public health and personal well-being in the United States. This study aims to examine whether the intersectionality hypothesis can be used in conjunction with the cumulative advantage (disadvantage), persistent inequality, or age-as-leveler to explain heterogeneity in low vision trajectories across birth cohorts, race or ethnicity, gender, and the level of education. Methods: Growth curve modeling was used to analyze data from the 2002–2014 Health and Retirement Study. Results: The type of trajectory (i.e., cumulative advantage or disadvantage, the persistent inequality, and the age-as-leveler) that characterize low vision is largely dependent upon the characteristics of an individual (i.e., race or ethnicity, gender, and education). Discussion: Trajectories of low vision are higher among females and those from ethnic minority groups with low levels of education. Implications for practitioners: Targeted interventions and attempts to close interethnic disparities in vision functioning should begin early on in life and should focus on racial ethnic minorities, females, and those with low education.